One crazy summer - Williams-García, Rita (SCHOLASTIC INC., 2012)
Set during one the most tumultuous years in recent American history, one crazy summer is the heartbreaking, funny tale of three girls who travel to Oakland, California, in 1968 in search of the mother who abandoned them. It's an unforgettable story told by a distinguished author of books for children and teens, Rita Williams-Garcia.